3D inkjet printing of electronics using UV conversion - Saleh, Ehab; Zhang, Fan; He, Yinfeng; Vaithilingam, Jayasheelan; Fernandez, Javier Ledesma; Wildman, Ricky D.; Ashcroft, Ian; Hague, Richard J.M.; Dickens, Phill; Tuck, Christopher (Wiley, 2017)
The production of electronic circuits and devices is limited by current manufacturing methods that limit both the form and potentially the performance of these systems. Additive Manufacturing (AM) is a technology that has been shown to provide cross sectoral manufacturing industries with significant geometrical freedom. A research domain known as Multi-Functional Additive Manufacturing (MFAM) in its infancy looks to couple the positive attributes of AM with application in the electronics sector could have a significant impact on the development of new products, however there are significant hurdles to overcome. This paper reports on the single step MFAM of three dimensional (3D) electronic circuitry within a polymeric structure using a combination of conductive and non-conductive materials within a single material jetting based AM system. The basis of this breakthrough is a study of the optical absorption regions of a silver nanoparticle (AgNP) conductive ink which lead to a novel method to rapidly process and sinter silver nanoparticle inks in ambient conditions using simple UV radiation contemporaneously with UV-curing of deposited polymeric structures.